Dissecting Cowpea Genetic Variability under Moisture Stress Conditions and Implications for Drought Tolerance Breeding - Mary Singini; Michael M. Chipeta; Keston Njira; Lameck Fiwa (International Journal of Agronomy)
Cowpea remains a crop of choice by most smallholder farmers particularly in arid and semiarid areas of the world due to its reported resilience to drought. However, recent evidence suggests that drought is currently a major abiotic stress in arid and semiarid regions with major consequences on crop yields and quality. Developing better-adapted and drought-tolerant varieties remains a sure strategy to reduce crop yield loss among farmers. The objective of the study was to explore the genetic variability among a diverse set of cowpea genotypes and identify drought-tolerant genotypes for developing more productive and drought-tolerant varieties. A diverse panel of 315 cowpea genotypes was evaluated under water stress and nonstress conditions across two locations using an Alpha lattice design. Water stress was imposed at the flowering stage, and irrigation was done after depletion of 80% of available water. Nine drought tolerance indices (MP = mean productivity index, GMP = geometric mean productivity index, HM = harmonic mean, STI = stress tolerance index, YI = yield index, YSI = yield stability index, TOL = tolerance index, Yrr = yield reduction ratio, and SSI = stress susceptibility index) were calculated based on grain yield under water stress and nonstress conditions. A joint analysis of variance across locations for both water stress trials and nonstress trials exhibited highly significant differences (P<0.001) among the main effect of genotype (G), location (L), and the interaction (GL) for grain yield (kg/ha). The results indicated that the locations (environments) used in the study were distinct and the genotypes evaluated presented differentiated performance in response to environmental variations. Principal component analysis based on the rank correlation matrix and the Pearson product-moment correlation coefficient revealed that most of the drought tolerant indices (MP, GMP, HM, YI, and STI) used were highly correlated with yield under stress and nonstress conditions which suggested that they are ideal for selecting drought tolerant genotypes that are stable and high yielding. From the genotypes screened under both water stress and nonstress conditions across two locations, the rank sum of indices selected 10 genotypes (MWcp66, Vuli-1, TVu-13265, MWcp27, MWcp20, MWcp59, IT99K-573-1-1, IT98K-131-2, TVu-1482, and IT 99K-529-1) as the most drought tolerant genotypes. These genotypes are therefore good sources of drought tolerant traits and are ideal for inclusion in a crossing program aimed at developing more productive and drought tolerant cowpea varieties more, especially in arid and semiarid areas.